PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION BERBASIS MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS IV SD RK SANTA MARIA PAKKAT - Sudiro Alexander Xaverius Simamora; Patri Janson Silaban; Juliana; Regina Sipayung; Antonius Remigius Abi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research applies a group investigation type cooperative learning model based on audio video media. The group investigation type cooperative learning model is a learning model that emphasizes complex student choice and control with group division that requires students to use high student thinking skills by considering close friendships or shared interests in certain topics. The aim is to determine the effect of the group investigation type cooperative learning model based on audio-vidual media on student learning outcomes in class IV science and science subjects at SD RK Santa Maria Pakkat for the 2023/2024 academic year. The research method used is an experimental method with a quantitative research type. To obtain the data required a test instrument of 25 questions. The total research sample was 30 students based on the saturated sampling technique. To determine students' initial abilities, the research conducted a pretest with an average score of 55,73 which was in the poor category. The results of the Posttest have improved from the Pretest results given previously with the students' average score reaching 86,26 in the very good category. It can be said that the level of success in student learning outcomes has increased as evidenced by the results of the correlation coefficient test calculation, the results obtained were r_count ≥ r_tabel with results of 0,805 ≥ 0,361. Next, hypothesis testing is comparing the t_count≥ t_table values. The obtained value of t_count = 7,192 while t_table = 2,042. Because t_count ≤ t_table (7,192 ≥ 2,042) then H_a is accepted and H_o is rejected. Through the t-test, it can be concluded that there is a significant positive influence between the group investigation type cooperative learning model based on audio video media on student learning outcomes.